PENDIDIKAN POLITIK : SARANA DAN PELAKSANANNYA - NORSANTI (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2014)
This writing aims to explore understanding about political education that include means and its implementation in this state. Political education is a learning to raise political knowledge and develop political awareness of society. Political awareness is an observation about politics problem of the world with a certain point of view. The implementation of political education in Indonesia still face many obstacles because the institution that has role to realize political education for society still not maximal to realize its role in process to educate societypolitically.